2015
DOI: 10.1159/000381559
|View full text |Cite
|
Sign up to set email alerts
|

Twelve Core Template Prostate Biopsy is an Unreliable Tool to Select Patients Eligible for Focal Therapy

Abstract: Introduction: To determine whether unilateral prostate cancer diagnosed at 12-core prostate biopsy harbours relevant prostate cancer foci in contralateral lobe in cases eligible for hemiablative focal therapy. Material and Methods: We analysed 112 radical prostatectomies of unilateral Gleason 6/7 prostate cancer based on prostate biopsy information. The presence of significant prostate cancer foci and/or the index lesion in the contralateral lobe is described. A subanalysis is performed in cases of Gleason sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…[11][12][13][14][15][16][17][18] Two of these studies reported on the rate of bilateral csCaP on WMP (33% and 50%, respectively) in patients with only unilateral disease on TRUS biopsy alone. [11][12][13][14][15][16][17][18] Two of these studies reported on the rate of bilateral csCaP on WMP (33% and 50%, respectively) in patients with only unilateral disease on TRUS biopsy alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13][14][15][16][17][18] Two of these studies reported on the rate of bilateral csCaP on WMP (33% and 50%, respectively) in patients with only unilateral disease on TRUS biopsy alone. [11][12][13][14][15][16][17][18] Two of these studies reported on the rate of bilateral csCaP on WMP (33% and 50%, respectively) in patients with only unilateral disease on TRUS biopsy alone.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14][15][16][17] Although there is strong clinical evidence that prostate imaging with mpMRI and targeted biopsy improves csCaP detection on the patient level, [18][19][20][21][22][23] to our knowledge the detection sensitivity for mpMRI for individual CaP foci remains moderate, particularly in smaller, nonindex, multifocal lesions. Appropriate candidates for hemiablation have csCaP limited to 1 prostate lobe.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 However, determination of GS is based on transrectal ultrasoundguided prostate biopsy, which is associated with sampling error and severe adverse events; [8][9][10] in particular, upgrading a patient with a higher GS from biopsy to prostatectomy specimen occurs in up to one-third of patients. 11,12 Recently, multiparametric magnetic resonance imaging (mpMRI), including diffusion-weighted imaging (DWI), has emerged as an important modality in prostate cancer diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it lacks the ability to precisely characterise the site, extent and grade of tumours identified [2], although availability of accurate information is obviously preferable when planning patient management. Transperineal template guided saturation biopsy (TPSB) has been introduced in an attempt to overcome the failings of conventional biopsy [3,4], but with a wide variation in reported incidence of retention, added cost concerns and uncertainty regarding optimum anaesthetic requirements [5,6]. Furthermore, patients and clinical governance bodies are increasingly expecting greater information to be supplied routinely regarding what individuals are likely to experience when undergoing any interventional procedure, but although prospective in-depth data are often lacking.…”
Section: Introductionmentioning
confidence: 99%